Impact of Salmonella FimH Gene Insertion on Lactobacillus plantarum Growth and Expression for Oral Vaccine Development - Nazir, Junaid; Ahmad Khan, Shabir; Nabi Magray, Suhail; Jha, Priyanka; Ahmad, Syed Mudasir (Journal of Neonatal Surgery, 2025)
Salmonellosis poses a major threat to poultry health and food safety, driving the need for more effective and sustainable vaccines. In this study, we developed a recombinant Lactobacillus plantarum-based oral vaccine expressing the Salmonella FimH antigen to induce mucosal and systemic immunity in poultry. The pTRK892 shuttle vector was engineered to include a constitutive promoter (Ppgm1), a signal peptide (SP1), and anchoring motifs for efficient antigen expression and secretion. The recombinant plasmids (pTRK722 and pTRK722FimH Histag) were successfully transformed into L. plantarum, confirmed by PCR, restriction mapping, and sequencing. Western blot analysis verified the expression and secretion of the FimH fusion protein. Growth curve analysis revealed a moderate metabolic burden on recombinant strain, reflected in a slightly reduced growth rate compared to the control. This recombinant vaccine platform offers a safe, cost-effective, and scalable alternative for poultry immunization, with the potential to reduce Salmonella colonization and transmission, ultimately enhancing food safety and public health.